KADAR PROTEIN DAN BOBOT DAGING PUYUH SETELAH PEMBERIAN BAHAN TAMBAHAN PAKAN TEPUNG IKAN SWANGI DAN PERIODISASI WAKTU PEMBERIAN TEPUNG KUNYIT YANG BERBEDA PADA RANSUM - Kartikayudha, W.; Isroli, Isroli; Suprapti, N H (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
The objectives of this study were evaluate the dietary of swangi fish meal and turmeric powder on protein content and weight of of pectorales and femorales of quail meat. Â Research was conducted based on 2x3 of factorial completely randomized design, in which the first factor was 2 levels of type diet, i.e. RA : standard diet; RB : 85% standard diet + 15% swangi fish meal, and the second factor was 3 levels of period time of turmeric powder addition, i.e. P0 : without turmeric powder; P1 : turmeric powder 54 mg/quail/day was given since quail age 210 days old for a month; P2 : turmeric powder 54 mg/quail/day was given since quail age 14 days old until the end of the observation (9 months old). The collected data were analyzed by analysis of variance. Duncanâ€™s Multiple Range Test was performed for mean comparison with 95% significance levels. All statistical analysis were performed using SAS software version 9.0 for windows. The results showed that dietary swangi fish meal increased crude protein level in the pectorales dan femorales of quail meat, whereas different period time of turmeric powder addition also increased crude protein level in the pectorales dan femorales of quail meat. Dietary swangi fish meal and different period time of turmeric powder addition resulted in interaction effect on crude protein level in the pectorales dan femorales of quail meat, but they did not result interaction effect on weight of of pectorales and femorales of quail meat.